Relação entre a atividade física voluntária na roda e a capacidade intrínseca para o exercício na esteira em animais não treinados - Iula Lamounier Lucca (2013)
Extrinsic and intrinsic factors influence the physical performance which one is analyzed in running tests performed on the treadmill either on the wheel in animal model studies. Hence it's important to investigate whether there are associations between both performances. Thus, the goal of this study were to compare the performances during treadmill running and wheel running between rats who presented intrinsic differences in treadmill running. Initially, 73 untrained rats performed three speed-ramped treadmill-running tests (TRT), whereby we determined the intrinsic capacity to run on the treadmill and also obtained performance data. We considered low capacity animals (LC), medium capacity animal (MC) and high capacity animals (HC) those whose maximal exercise's time (ETmax ) in TRT were, respectively, < 24.9 min; between 24.9 and 57.1 min and > 57.1 min. Subsequently 11 rats of each group (LC; MC and HC) were given 11 days access to activity wheels which afforded their daily variables wheels performance. Data were analyzed by statistical parametric and presented as mean ± standard error, or nonparametric and presented as median. The results indicated differences between the three groups in the treadmill performance ( LC < MC < HC, p < 0.05 ). The ETmax of LC group was 20.2 ± 1.4; MC: 41.2 ± 1.9 and HC: 69.0 ± 2.2 min; the maximum values of distance (Dtreadmill) of LC was 295.4; MC: 654.6 and HC: 1,394.6 m; the work (Wtreadmill) of LC was 6.6; MC: 16.4 and HC: 35.7 kgm and the speed (Streadmill) LC was 16.2 ± 0.5, MC: 23.3 ± 0.6 and HA: 32.4 ± 0.7 m/min. However, the speed's moment which the rats stopped the treadmill running for the first time (V1ª Stop, m/min ) was lower in LC: 12.2 ± 0.7 (p < 0.05) and equal among the other MC: 16.4 ± 1.6 and HC: 18.9 ± 1,2 (p > 0.05). The wheel performance was similar between groups in all variables, when analyzed daily averages, and the average of the daily distance (Dwheel) LC: 1,164.9; MC: 736.1; HC: 994.6 m/day (p = 0.072), the daily work (Wwheel ) LC: 174.7; MC: 110.4; HC: 149.2 J/day (p = 0.072), the daily maximum speed (Smax wheel) LC: 101 ± 5.5; MC: 100 ± 3.1 and HC: 110.2 ± 4.2 m/min (p = 0.210) and the daily average speed (Smed wheel) LC: 16.1 ± 1.1; MC: 15.1 ± 0.8 and HC: 16.2 ± 1.4 m/min (p = 0.740), no differences were found in the minimum and maximum values of all these variables, and also in the distance and work sum of the period the wheel access (p > 0.05). The over time analysis showed similarity between the groups (p > 0.05) in over days distance's increases and also in their circadian pattern in wheel. The correlation analysis performed with all animals jointly showed that the Smax wheel were positive and weakly associated with both Dtreadmill (r = 0.354 , p = 0.043) and the Wtreadmill (r = 0.368, p = 0.035). Although the intragroup analysis showed in the LC group a negative and moderate association between the average Smed wheel and the S1ª Stop (r = 0.669, p = 0.024), and in the MC group several positive associations, such as: ETmax, Dtreadmill and Streadmill were positive and moderately associated to the average, maximum and minimum values of Dwheel (r between 0.63 and 0.69, p < 0.05) and strongly associated with the D11 days of the running wheel (r between 0.73 and 0.77, p < 0,05), which in turn also were strongly associated with the D3 tests of running treadmill (r = 0.078, p < 0.05) and with the S1ª Stop on the treadmill (r = 0.086, p < 0.001). We concluded that despite the similarity in the wheel running performance between the groups of rats that presented intrinsic differences in the ability to treadmill running, the performance of the two running modality can be related, especially in animals with medium capacity for treadmill running.